Kur’an-ı Kerim’de akrabalık kavramı - Şahan, Ramazan (My University, 2010)
Anahtar KelimelerAkraba, Hısım, Âile, Baba, Anne, Karı, Koca, Çocuk, Dede, Torun, Süt, Neseb, Nikah, Evlilik, Mîrâs TEZ ÖZETİ KUR'ÂN-I KERÎM’DE AKRABALIK Kur’ân bütün insanların aynı soydan, bir erkek ve bir dişiden yaratıldığını vurgular. Bütün insanlar eşit olup kimse kimseden üstün değildir. Üstünlük inanç ve ahlaktadır. Araştırmamı bir giriş ve üç bölümden oluşmaktadır. Girişte araştırmanın konusu, önemi ve amacı ile metodu anlatılmaktadır. Birinci bölümde akrabalıkla ilgili kavramlar anlatılmaktadır. Bunlardan yakınlık “ulu’l-kurbâ/ yakınlık sahipleri” ile “akrabûn” kavramları bir başlık altında; akrabalıkla dolaylı olarak ilgili olan “ulu’l-erhâm”, “velâyet” kavramları ile “nikâh, radâ’, zürriyet, sulb, neseb, sıhr, ehl/ âl, ‘asabe, kabîle-aşîret, şu’ûb-kavim, ümmet ve millet” kavramları da bir başlık altında izah edilmiştir. İkinci bölüm akrabalığın çekirdeğini oluşturan âile ile âilenin genişletilmiş şekli olan akrabalığı konu edinmektedir. Burada öncelikle âilenin tanımı, çeşitleri ve fonksiyonları ile âilenin birinci dereceden fertleri ele alınmaktadır. Kur'ân’ın öngördüğü âiledeki “eşler, anne-baba ve çocuklar (torunlar) ile kardeşler” anlatılmaktadır. Ayrıca “Âileye Mülhak Olan Guruplar” başlığında da neseb, süt ve evlilik yoluyla oluşan akrabalar izah edilmektedir. Üçüncü bölümde akrabalığın meydana getirdiği sonuçlar anlatılmaktadır. Burada “Hukûkî Sonuçlar” başlığı altında mahremiyet, mîrâs ve vasıyyet, nafaka, ganimet, velâyet, şehâdet ve adalet ile akrabalığın cinayetlere etkisi tartışılmakta; her bir başlık kendi içinde alt başlıklara ayrılarak anlatılmaktadır. İçtimâî-Ahlâkî Sonuçlar kısmında sıla-i rahim konusu ve bunu meydana getiren diğer yan unsurlar ile taassub konusu ele alınmaktadır. Bunun alt başlıkları olarak âile, aşîret ve ırk taassubu işlenmektedir. “Uhrevî-Manevî Sonuçlar” kısmında ise akrabalara dua etmek, manevî yolculuğa uğurlarken yapılması gereken işlemler ile yakınlara şefaat konusu anlatılmaktadır. Burada suç ve cezanın şahsîliği ve İslam’a göre kimsenin bir yakınının vebalini üstlenemeyeceği konusuna vurgu yapılmaktadır.

KEY WORDS: Relative or relationship, in law or relative (ex: mother in law: kaynana), family, dad, or father, mom, mother, wife, husband, kid, child, grandfather, grandchild, milk, ancestry, lineage, marriage ceremony, marriage, natrimony, inheritance THE RELATİONSHİP İN THE HOLY QOURAN The Quran emphasize that all humankind has been created by the same lineage and one male and one female. Also, all humankind is equal and no one has priority over the other one. The priority is in the belief and morality. Our research occurs by one introduction and three chapters, In the introduction, the subject, importance and the aim of the research has been explained. In the first chapter, the concepts which are related to relationship has been explained. Under a title, From These concepts which are those who have closeness (ulu’l-kurbâ) the other concept which is relatives (akrabûn), has been explained, and under another title “ulu’l-erhâm” which is related to relationship indirectly, the concepts which are “law guardianship/ velayet”, “marriage/ nikah, radâ”, “progeny/ zürriyet”, “sulb”, “ancestry/ nesep” “sıhr”, ehl/ âl, “asabe” “tribe/ kabîle-aşîret, “şu’ûb-kavim, ümmet/ Islam the Community of the faithful, the worldwide Muslim Community and millet/ nation ” has been explained. The second chapter includes the family which forms the nucleus of the relationship, and includes relationship that is a wide form of the family. In this part, firstly, by the persons who is the first rank of the family, and the definition, varieties, and functions of the family, has been considered. As the Holy Quran envisages wifes and husband, mother and father, kids (descendants) and brothers of the family has been explained. In addition under the title which is “the groups which are law annexation to the family”, ancestry, and the relationships which occurs by the marriage and milk has been explained. In the third part, the results of which the relationship has been occured. Here, under the the title “the results relating to law” confidentiality(mahremiyet), inheritence(miras), last request(vasiyet), law maintenance allowance(nafaka), booty(ganimet), law guardianship(velayet), the Islamic doctrinal Formula(şahadet), and the effects to the murder of justice(adalet), and the relationship, and every single title is being argued by dividing them as subtitles. In the chapter of social and moral (İçtimâî-Ahlâkî) results, the issue of sıla-i rahim and the consequences which are side elements by which are occured, and taassub(fanaticism) issue has been expressed. As subtitles of this, family, tribe, and race fanaticism(taassup) has been penetrated. In the part of “otherworldly(uhrevi) and spiritual(manevi)” praying for relationships, the procedure which are necessary while burrying someone, and intercession for relatives. Also, here, it is told that the crime and punishment is personal. Here it is emphasized that the crime and punishment cannot be accepted by someone who is relative to the guilty, according to Islam.
Keywords: Akrabalık_Din; Evlilik; İslam Dini; Kur’an-ı Kerim